Procognitive, Anxiolytic, and Antidepressant-like Properties of Hyperoside and Protocatechuic Acid Corresponding with the Increase in Serum Serotonin Level after Prolonged Treatment in Mice - Jolanta Orzelska-Górka; Katarzyna Dos Santos Szewczyk; Monika Gawrońska-Grzywacz; Mariola Herbet; Anna Lesniak; Anna Bielenica; Magdalena Bujalska-Zadrożny; Grażyna Biała (Pharmaceuticals, 2023)
Two polyphenols–hyperoside (HYP) and protocatechuic acid (PCA) were reported to exert antidepressant activity in rodents after acute treatment. Our previous study also showed that this activity might have been influenced by the monoaminergic system and the upregulation of the brain-derived neurotropic factor (BDNF) level. A very long-term pharmacological therapy is required for the treatment of a patient with depression. The repetitive use of antidepressants is recognized to impact the brain structures responsible for regulating both emotional and cognitive behaviors. Thus, we investigated the antidepressant, anxiolytic, and procognitive effects of HYP and PCA in mice after acute and prolonged treatment (14 days). Both polyphenols induced an anxiogenic-like effect after acute treatment, whereas an anxiolytic effect occurred after repetitive administration. PCA and HYP showed procognitive effects when they were administered acutely and chronically, but it seems that their influence on long-term memory was stronger than on short-term memory. In addition, the preset study showed that the dose of 7.5 mg/kg of PCA and HYP was effective in counteracting the effects of co-administered scopolamine in the long-term memory impairment model induced by scopolamine. Our experiments revealed the compounds have no affinity for 5-HT1A and 5-HT2A receptors, whereas a significant increase in serum serotonin level after prolonged administration of PCA and HYP at a dose of 3.75 mg/kg was observed. Thus, it supports the involvement of the serotonergic system in the polyphenol mechanisms. These findings led us to hypothesize that the polyphenols isolated from Impatiens glandulifera can hold promise in treating mental disorders with cognitive dysfunction. Consequently, extended studies are necessary to delve into their pharmacological profile.